Long-term exposure to fine particulate matter, ozone, and greenness and the risk of lung cancer: a retrospective cohort analysis within a national sample cohort - Kim, Nam Eun; Lee, Ji-Young; Lee, Ga Young; Lee, Chai Young; Park, Sojung; Ryu, Yon Ju; Lee, Jin Hwa (Frontiers in Public Health, 2025)
Background and objectiveGiven the rising incidence of lung cancer among never smokers and growing concerns about environmental risk factors, this study investigated the association between long-term exposure to air pollution and greenness and the risk of lung cancer.MethodsWe conducted a retrospective cohort analysis using data from the Korean National Sample Cohort (2002–2019), including 7,155 lung cancer patients and 28,620 propensity score-matched controls (matched by age, sex, and enrollment year). Long-term exposure to air pollution (quantified by PM2.5 and O₃ concentrations) and greenness (quantified by the normalized difference vegetation index, NDVI) was estimated based on residential area. Cox proportional hazards models were used to assess associations between exposure and lung cancer risk.ResultsAmong 35,775 participants, lung cancer patients had lower BMI, higher smoking exposure, lower household income, and higher comorbidity scores than controls. PM2.5 exposure showed a modest association with increased lung cancer risk in the highest tertile (aHR = 1.06; 95% CI = 1.01–1.13). O₃ exposure was consistently associated with elevated risk across all tertiles (aHR = 1.42; 95% CI = 1.34–1.50). Greenness exposure demonstrated a protective effect (aHR = 0.89; 95% CI = 0.86–0.91). Subgroup analyses indicated that PM2.5 effects were more pronounced among male never smokers, O₃ exposure was associated with higher risk in female never smokers and males overall, and NDVI showed protective associations across all subgroups.ConclusionLong-term exposure to air pollution, particularly O₃, was significantly associated with an increased risk of lung cancer, independent of other confounders. In contrast, PM2.5 showed only a modest and inconsistent association, while high greenness exposure demonstrated a protective effect. These findings emphasize the need for region-specific environmental policies aimed at improving air quality and enhancing access to green spaces to reduce lung cancer risk.